(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: An irreversible hydrocolloid impression material combined with two different doses of chlorhexidine solution is tested for dimensional change and tearing strength. The aim of this study is to evaluate the impact of adding chlorhexidine with 2 different available concentrations on alginate impression material. Materials and Methods: According to the manufacturer’s instructions, the irreversible hydrocolloid specimens is made and divided into 3groups (Group 1 is mixed with tap water as a control group, Group 2 is mixed with 0.12 chlorhexidine, and Group 3 is mixed with 0.2 chlorhexidine). Testing is done on the change in dimensions and the tearing strength. Results: Lesser dimensional change is observed at group two and is non-significant, and the group three is significantly more dimensionally stable when compared with group one, tearing strength of group one and two is nearly the same while the group three is more resistant to tear and the difference is significant Conclusion: The dimensional stability and tearing resistance of chlorhexidine self-disinfecting irreversible hydrocolloid impression material may vary greatly.